Agile development model for certifiable medical device software - Erica Esmeraldo Figueiredo Lima (2020)
This study aims to illustrate how is the current state when the subject is medical device software using agile. Introduces the needs of the regulations and the standards to be a certifiable medical device software and how this is the safer and quality way to do it. The problem that many companies feel obligated to use the waterfall still when it is a project too complex or have many regulations as the only way to build software. The medical area is not different; it is challenging to put agile and still comply with all regulations and standards. This paper will illustrate some works that other papers have already done using agile and try to find the best way to proceed by validation, through one academic case and interviews and finally contribute with a final proposed process. Keywords: Agile development, Agile methodologies, Medical device, Scrum, Process, Regulation, Software life cycle processes, Risk Management, Software Process Improvement (SPI), FDA, Medical device industry.